Innovation in Social Services A Systematizing Overview based on the EU Research Platform INNOSERV - Langer, Andreas; Eurich, Johannes; Güntner, Simon; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
Across Europe, there is an intense search for new and sustainable approaches to providing welfare. Demographic change, new social risks and other factors call for new ideas to maintain and enhance the performance and quality of social services and to enable the participation of all citizens in an inclusive society. Against this background, and based on the findings of the EU research platform INNOSERV and empirically obtained research results from text and video material, this book provides insights into current approaches and practices to improve and transform social services. Content Innovation Actors and Practices • Innovation and Organisation • Innovation, Quality and Evaluation • User Orientation • Technology and Digitisation • Context Innovations Target Groups · Lecturers, students and professionals from the field of innovation and social service research · Managers and executives from social services and social economy · Social work, social management and innovation management The Authors Dr. Andreas Langer is Professor of Social Sciences, Social Policy and Sociology at HAW Hamburg and Managing Director of the German Institute for Social Economics (DISW). Dr. Johannes Eurich is Professor of Practical Theology/Diaconal Science at the University of Heidelberg and Director of the Institute of Diaconal Studies at the University of Heidelberg. Dr. Simon Güntner is Professor of Spatial Sociology at TU Wien. Videos via App: Download the Springer Nature More Media App for free - scan images in the book via App with mobile phone or tablet to stream videos.
Innovation Actors and Practices -- Innovation and Organisation -- Innovation, Quality and Evaluation.-User Orientation -- Technology and Digitisation -- Context Innovations.
Keywords: Social structure; Equality; Economic sociology; Political science; Social Structure; Economic Sociology; Political Science